Comparison of 2g vs 1 g of Prophylactic Cefazolin in Surgical Site Infections in Trauma Surgery Below the Knee. (May 2020) - Sanders, Fay R. K.; Kistemaker, Rosanne M.G.; van 't Hul, Mirjam; Schepers, Tim
Background: The rate of surgical site infections (SSIs) after foot or ankle surgery remains high, despite the implementation of antibiotic prophylaxis. Recently, guidelines suggest a single dose of 2 g instead of 1 g of cefazolin for implant surgery; this decision is largely based on pharmacokinetic studies. However, the clinical effect of this higher dose has never been investigated in foot and ankle surgery. This retrospective cohort study investigated the effect of 2 g compared with 1 g of prophylactic cefazolin on the incidence of SSIs in foot and ankle surgery. Methods: All patients undergoing trauma-related surgery of the foot, ankle, or lower leg between September 2015 and March 2019 were included. The primary outcome was the incidence of an SSI. SSIs were compared between patients receiving 1 g and 2 g of cefazolin as surgical prophylaxis, using a propensity score to correct for possible confounders. Results: A total of 293 patients received 1 g and 126 patients received 2 g of cefazolin. The overall number of SSIs was 19 (6.5%) in the 1-g group and 6 (4.8%) in the 2-g group. Corrected for possible confounders, this was not statistically significant (OR, 0.770; P = .608). Conclusion: Even though the decrease in SSI rate from 6.5% to 4.8% was found not to be statistically significant, it might be clinically relevant considering the reduction in morbidity, mortality, and healthcare costs. Research linking pharmacokinetic and clinical results of prophylactic cefazolin is needed to establish whether or not the current recommendations and guidelines are sufficient for preventing SSIs in foot and ankle surgery. Level of Evidence: Level III, retrospective comparative series.